Australian veterinarians' perspectives on the contribution of the veterinary workforce to the Australian animal health surveillance system - Hayes, Lynne; Manyweathers, Jennifer; Maru, Yiheyis; Davis, Emma; Woodgate, Robert; Hernandez-Jover, Marta (Frontiers in Veterinary Science, 2022)
This study investigated the involvement of private veterinarians in surveillance activities and the veterinary workforce’s contribution to the Australian animal health surveillance system. The perception that there is overall a decreased engagement by veterinarians in surveillance outcomes at a time when there is increased need for bolstering of surveillance systems was investigated. Three key questions were considered: 1. What is the current contribution of private veterinarians to the Australian surveillance system? 2. What is the veterinary professions capacity to assume a more prominent role in surveillance? 3. What is the interest and ability of the veterinary profession in Australia to undertake this surveillance role now and into the future? Semi-structured telephone interviews were conducted with 17 private veterinarians with data analysed qualitatively to identify key themes. Results demonstrate that private veterinarians are aware of their responsibilities and are engaged in surveillance activities at both formal and informal levels. The key challenges associated with current and future contributions were related to workload, remuneration, conflicts of interest and shared responsibility. The study has demonstrated that even amongst an engaged population, barriers do need to be addressed if private veterinarians are to be tasked with increasing their involvement in animal health surveillance activities.